Réponses

2014-04-22T17:49:43+02:00
36-12x+x² = (6)²-2*6*x+(x)²

Cette expression est de la forme a²-2ab+b² avec a = 6 et b = x
Rappel : a²-2ab+b² = (a-b)²

36-12x+x² = (6-x)²

   36-12x+x^2+(3-4x)(6-x)
= (6-x)²+(3-4x)(6-x)
= (6-x)(6-x)+(3-4x)(6-x)

Tu remarques l'existence d'un facteur commun : 6-x

(6-x)(6-x)+(3-4x)(6-x) = (6-x)(6-x+3-4x) = (6-x)(-5x+9)

2014-04-22T17:55:16+02:00
Bonjour ,

Factoriser:
=36-12x+x²+(3-4x)(6-x)                                           [ 36 - 12x +x² = ( 6 - x)²  ]
= (6 -x)² +(3 - 4x) ( 6 - x)
=( 6 -x) [ (6 -x) +(3 - 4x)]
= ( 6 - x) ( 6 - x +3 -4x)
= (6 -x) ( 9 -5x)
Rappel :
(a - b) = a² - 2*a*b +b²
(a + b) = a² + 2*a*b +b²
a² - b² = (a - b) ( a + b)